O parto de mulheres quilombolas: contribuição para o cuidado de enfermagem na perspectiva de Madeleine Leininger - Araújo , Sandra Taveiros de (2017)
This research aimed at the experience of normal childbirth in the culture of quilombola women. Throughout the history of mankind, parturient assistance has undergone several modifications, thus, the experience of childbirth of a family and physiological event is considered a potential risk to the health of the mother and the baby, demanding hospitalization. In this process of transferring scenery to delivery and birth care, several cultural knowledges and beliefs have been replaced by hospital-centered practices of care and no longer centered on women and the family. As a consequence of the transposition of the parturition scenario, the excessive medicalization of delivery is observed, to the detriment of the needs arising from the social, economic, cultural, psychological and spiritual components that integrate human beings. This reductionism of the meaning of childbirth to purely biological aspects emphasizes the need to rethink the health of parturient women, considering also the cultural heterogeneity of the various ethnic groups in Brazil, such as the quilombolas, making it relevant to answer the following research question: How do quilombola women experience normal labor? The general objective of the research is to understand the experiences about the childbirth and birth of quilombola women, with the following specific objectives: to apprehend the experiences on the childbirth and birth of quilombola women; Identify culturally congruent care for quilombola women who experience childbirth and birth; And to analyze culturally congruent care for quilombola women who experience childbirth and birth. It was assumed that the experiences of quilombola women facing the phenomenon of childbirth suffer cultural influences from various segments that relate to their way of being and living in community. The methodological approach adopted was based on the comprehensivist approach of qualitative research, based on Madeleine Leininger's Theory of Diversity and Universality of Cultural Care. The Thematic Oral History was used as technical pole for information production. They emerged as Thematic Units of Significance: (1) Access and practices of attention to the reproductive health of quilombola women during the pregnancy period, was weakened by the deficiency in the communication between the antenatal care and childbirth and delivery interfaces, leading to the quilombola woman experiences a feeling of fear and insecurity arising from the pilgrimage in the obstetric care network, given the real risk of maternal and neonatal morbidity and mortality; ; (2) Local knowledge about childbirth and birth comes mainly from intergenerational transmission, especially among women in the community and from the knowledges and practices of the traditional part; (3) Cultural values about childbirth and birth, beliefs and rites were present in reports about the universe that permeates the experience of childbirth and birth of quilombola women, highlighting those related to the presence of the divine in the act of birth and its opposite, the Profane, expressed through taboos aimed at the perception of vular debris, specifically the placenta. All units of thematic analysis were reflected in the theoretical framework and presented internal coherence with the postulates and assumptions proposed by Madeleine Leininger, allowing us to envisage possibilities for a nursing care that is congruent with the culture of Quilombola women in Muquém. As final considerations, it was observed that for Quilombola women in Muquem, the experience of childbirth and birth is unique, special, unforgettable and often refers to ambiguous feelings related to fear, anxiety and tension, on the one hand; And with pleasure, happiness and satisfaction for another. The duality between the positive and negative feelings seized from these experiences was related to the various influences of the dimensions and interfaces involved in the socio-historical-cultural context and worldview of quilombola women. It is hoped that the results of this study contribute to the approximation of nursing knowledge and cultural practices that permeate the experience of childbirth by quilombola women, with a view to the promotion of nursing care to these pregnant women based on culturally congruent care.